Disunion! : The Coming of the American Civil War, 1789-1859 - Varon, Elizabeth R. (Book collections on Project MUSE., 2010)
Varon blends political history with intellectual and cultural history to examine the ongoing debates over disunion that long preceded the secession crisis. She focuses not only on politicians but also on a wide range of reformers, editors, writers, and commentators.